Моделі плоского руху двоколісного експериментального балансуючого зразка - Кулік, А.С.; Дергачов, К.Ю.; Пасічник, С.М. (Проблемы управления и информатики, 2022)
Предметом вивчення в статті є процес формування моделей плоского руху двоколісного експериментального балансуючого зразка (ДЕБЗ). Метою є розробка підходу до формування моделей плоского руху ДЕБЗ як об’єкта управління. Наукова новизна полягає у формуванні підходу щодо отримання моделей поступального та кутового рухів ДЕБЗ на площині, що відрізняється від відомих повнотою обліку діючих сил і моментів. The subject of the study in the article is the process of forming models of planar motion of a two-wheeled experimental balancing prototype (TWEBP). The aim is to develop an approach to forming models of the planar motion of the TWEBP as a control object. The following tasks are set: to form a physical model of the TWEBP; to develop a nonlinear mathematical description of the translational and rotational motion of the TWEBP in the plane using Lagrange formalism; to obtain the control object description in the frequency domain using Laplace transforms; to obtain the linearized mathematical description of the control object in the state space; to form graphical models of the TWEBP as a control object using block diagrams in both time and frequency domains; to form conditions for the use of mathematical descriptions as mathematical models of the control object. The methods used include: the Lagrange method, analytical linearization, state-space method, and Laplace transforms.